Mechanisms of Infectivity and Evasion Derived from Microvesicles Cargo Produced by Trypanosoma cruzi - Borges, Bruna C.; Uehara, Isadora A.; Dias, Laysa O. S.; Brígido, Paula C.; da Silva, Claudio V.; Silva, Marcelo J. B. (Frontiers in Cellular and Infection Microbiology, 2016)
Cell invasion by the intracellular protozoans requires interaction of proteins from both the host and the parasite. Many parasites establish chronic infections, showing they have the potential to escape the immune system; for example, Trypanosoma cruzi is an intracellular parasite that causes Chagas disease. Parasite internalization into host cell requires secreted and surface molecules, such as microvesicles. The release of microvesicles and other vesicles, such as exosomes, by different eukaryotic organisms was first observed in the late twentieth century. The characterization and function of these vesicles have recently been the focus of several investigations. In this review, we discuss the release of microvesicles by T. cruzi. The molecular content of these vesicles is composed of several molecules that take place during parasite-host cell interaction and contribute to the parasite-driven mechanism of evasion from the host immune system. These new findings appear to have a profound impact on the comprehension of T. cruzi biology and highlight novel potential strategies for developing more efficient therapeutic approaches.